Platelet Functions are Decreased in Obesity and Restored after Weight Loss: Evidence for a Role of the SERCA3-Dependent ADP Secretion Pathway - Elaïb, Ziane; Lopez, Jose Javier; Coupaye, Muriel; Zuber, Kevin; Becker, Yann; Kondratieff, Aurélie; Repérant, Christelle; Pépin, Marion; Salomon, Laurence; Teillet, France; Msika, Simon; Denis, Cécile V.; de Prost, Dominique; Rosa, Jean-Philippe; Bobe, Régis; Stépanian, Alain (Thrombosis and Haemostasis, 2019)
In obesity, platelets are described as hyperactive, mainly based on increased platelet size and presence of pro-thrombotic plasmatic molecules. We explored platelet functions, including calcium signalling in obesity, and the effect of weight loss. We included 40 obese patients (women with body mass index [BMI] of ≥ 35 kg/m2) who were to undergo gastric bypass surgery and 40 healthy lean subjects (women with BMI of < 25 kg/m2) as a control group. Approximately 1 year after surgery, the obese patients lost weight (75% had a BMI < 35 kg/m2). They were explored a second time with the same healthy control for the same platelet experiments. Compared with controls, obese patients' platelets displayed reduced sensitivity to thrombin (aggregation EC50 increased by 1.9 ± 0.3-fold, p = 0.005) and a lower Ca2+ response (70 ± 7% decrease, p < 10−4). In 17 pairs of patients, we performed additional experiments: in obese patients' platelets, thrombin-induced αIIbβ3 activation was significantly lower (p = 0.003) and sarco-endoplasmic reticulum Ca2+ATPase (SERCA3) expression was decreased (48 ± 6% decrease, p < 10−4). These differences were abolished after weight loss. Interestingly, pharmacological inhibition of SERCA3 activity in control group's platelets mimicked similar alterations than in obese patients' platelets and was associated with defective adenosine diphosphate (ADP) secretion. Addition of ADP to agonist restored platelet functions in obese patients and in SERCA3-inhibited control platelets (five experiments) confirming the direct involvement of the SERCA3-dependent ADP secretion pathway. This is the first study demonstrating that platelets from obese patients are hypo-reactive, due to a deficiency of SERCA3-dependent ADP secretion. Weight loss restores SERCA3 activity and subsequent calcium signalling, αIIbβ3 activation, platelet aggregation and ADP secretion.
Keywords: platelets; obesity; SERCA3; bariatric surgery; calcium